Quercetin supplementation promotes recovery after exercise-induced muscle damage: a systematic review and meta-analysis of randomized controlled trials - Daniel Rojano-Ortega; José Peña-Amaro; Antonio Berral-Aguilar; Francisco Berral-de la Rosa (Termedia Publishing House, 2022)
Quercetin (Q) is one of the most frequently consumed flavonoids in the human diet. The purpose of this systematic review and meta-analysis was to determine the effects of Q supplementation on muscle damage, muscle soreness and biochemical markers of inflammation, antioxidant capacity and oxidative stress after intense exercise. A literature search of SPORTDiscus, PubMed, Web of Science and Scopus was performed from inception to May 31, 2022. Forest plots were generated with fixed or random-effect models and standardized mean differences (SMD). Data extraction and quality assessment were performed independently by two authors. After application of the inclusion and exclusion criteria, 13 studies with a total of 249 sedentary to well-trained participants were included. For all studies there were some concerns about the risk of bias. All but one study used a supplementation dosage of 1000 mg/day. Q supplementation accelerated recovery of muscle function and significantly decreased muscle soreness 0/24 h after exercise (SMD: -1.33; p = 0.03), creatine kinase levels 24/48 h after exercise (SMD: -1.15; p = 0.02), and post-exercise oxidative stress (SMD: -0.92; p = 0.03). However, Q supplementation had no effect on IL-6 concentration. Q supplementation with a dose of 1000 mg/day for periods of more than seven days and a maximum of 12 weeks appears to be a safe and efficacious strategy to reduce muscle damage and muscle soreness, as well as to enhance recovery after intense exercise in sedentary to well-trained young men. Systematic review registration: PROSPERO CRD42021266801.